(untitled) - LINCOLN D JONES (Austin, Texas, 1999)
This book reviews the essential material in: basic fundamentals; power distribution; control systems; digital systems; machinery; electronics; computing; communication systems; biomedical instrumentation and safety, plus an appendix on engineering economic analysis
Keywords: electrical engineering; problems, exercises, etc